2017
DOI: 10.1177/0886260517691520
|View full text |Cite
|
Sign up to set email alerts
|

Cambodian Remarried Women Are at Risk for Domestic Violence

Abstract: Divorce rates continue to rise, especially in urban centers, which in turn contributes to increasing numbers of women who remarry. While remarriage is one of the only options for survival for divorced women, especially those from low socioeconomic status, remarriage also brings with it increased stressors of financial strain and the strain of blended families. This study tested the hypothesis that remarried women compared with first-time married and divorced women are at increased risk for domestic violence. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 27 publications
(28 reference statements)
0
18
0
1
Order By: Relevance
“…Recent scholars have identified only slight increases in divorce rates in Cambodia over time and across cohorts, since before the KR regime through cohorts married by 1999 (Hueveline & Poch, ), and a higher risk for intimate partner violence in remarriages in Cambodia (Eng, Szmodis, & Grace, ). To extend the sociointerpersonal perspective of PTSD, a question to address, aside from whether individuals are married, is their relationship quality and the support they have received from their intimate relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Recent scholars have identified only slight increases in divorce rates in Cambodia over time and across cohorts, since before the KR regime through cohorts married by 1999 (Hueveline & Poch, ), and a higher risk for intimate partner violence in remarriages in Cambodia (Eng, Szmodis, & Grace, ). To extend the sociointerpersonal perspective of PTSD, a question to address, aside from whether individuals are married, is their relationship quality and the support they have received from their intimate relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Attention to remarriage and stepfamily formation in Asian societies has been sporadic and limited to specific contexts such as East Asia (see Hu & To, 2018; Kim, 2010; Lam-Chan, 1999; Nozawa, 2015; Tai, Wan et al, 2008; Webber, 2003) attributed to the invisibility of and stigma against family structures that are not first marriage, nuclear family units in Asian societies (Neo, 2006; Nozawa, 2015; Webber, 2003). Constructions of moral panic around non-biological relationships within stepfamilies have prompted from time to time alarmist reports of abuse that relegate such family units as problems or deficits with a less than ideal milieu for raising children from previous unions (Eng et al, 2017). Yet, in other instances, re-partnerships and remarriages are sought as a pragmatic option to overcome dire economic conditions and family instability, and reintegrating into mainstream society (Dewilde & Uunk, 2008; Faroo, 2012b; Ozawa & Yoon, 2002).…”
Section: Comparative Themes: Lessons From the Westmentioning
confidence: 99%
“…The analysis [37] using the 2005 demographic and health survey has revealed that 20% of remarried women experienced emotional violence and 14% experienced physical violence. These women were more likely to experience emotional and physical violence in their second marriage [37].…”
Section: Literature Reviewmentioning
confidence: 99%